Comparison of Diagnostic Criteria for Common Variable Immunodeficiency Disorder - Ameratunga, Rohan; Brewerton, Maia; Slade, Charlotte; Jordan, Anthony; Gillis, David; Steele, Richard; Koopmans, Wikke; Woon, See-Tarn (Frontiers in Immunology, 2014)
Common Variable Immunodeficiency disorders (CVID) are the most frequent symptomatic primary immune deficiency condition in adults. The genetic basis for the condition is not known and no single clinical feature or laboratory test can establish the diagnosis: it has been a diagnosis of exclusion. In areas of uncertainty, diagnostic criteria can provide valuable clinical information. Here we compare the revised European Society of Immune Deficiencies (ESID) registry (2014) criteria with the diagnostic criteria of Ameratunga et al (2013) and the original ESID/ Pan American Group for Immune Deficiency (ESID/PAGID 1999) criteria. The ESID/PAGID (1999) criteria either require absent isohemmagglutinins or impaired vaccine responses to establish the diagnosis in patients with primary hypogammaglobulinemia. Although commonly encountered, infective and autoimmune sequelae of CVID were not part of the original ESID/PAGID (1999) criteria. Also excluded were a series of characteristic laboratory and histological abnormalities, which are useful when making the diagnosis. The diagnostic criteria of Ameratunga et al (2013) for CVID are based on these markers. The revised ESID registry (2014) criteria for CVID require the presence of sympt